Financialisation and economic growth in Africa - Kungwane, Reabetswe (Graduate School of Business (GSB), 2021)
Despite the growing literature on financial development-economic growth nexus, there exists a paucity of empirical studies that explore the impact of financialisation on economic growth while focusing on the competitiveness of the financial sector. This study examines the revealed comparative advantages of 34 developing African countries from the period 2008 to 2017 and goes further to determine the impact of the revealed comparative advantage indices on economic growth. Revealed comparative advantage is used as an alternative proxy to financialisation, while economic growth is measured in terms of GDP per capita. In order to determine the impact, a panel study approach was followed, using a multiple linear regression model. The study produces two findings. Firstly, we find that the majority of African countries do not reveal a comparative advantage in financial services. This finding confirms our expectation. Secondly, we find that there exists a negative and significant relationship between financialisation and economic growth. The findings suggest that as developing countries in Africa gain comparative advantages in financial services, those gains have a detrimental impact on their economic growth. Informed by the findings of this study, which have implications for financial market development in Africa, the main recommendations are firstly that regulators need to play their part in reducing the cost of business for financial services institutions—particularly compliance costs, so as to encourage competition and development in the financial services sector, without compromising their responsibility to protect consumers. Secondly, better insights regarding cross-border trading and its impact on economic growth, profitability and the accumulation of foreign currency reserves need to be gained, in order to come up with more conducive regulatory frameworks that do not result in penalties for local firms, rendering them uncompetitive relative to foreign firms. Additionally, management at financial institutions have the responsibility of ensuring that benefits derived from their cross-border business go beyond shareholder value, but that reinvestment into the real economy takes place either through increased lending or equity investments and should also ensure that sufficient investments are made into the infrastructure required to increase the institution's competitiveness. Finally, Government and regulators needs to pay attention to how cross-border financial transactions are taxed, especially considering the new era of FinTech's, cryptocurrencies, and deepening regional integration, while at the same time ensuring that there is greater depth, bread and liquidity of their local financial markets.